Exploring FlyBase Data Using QuickSearch. Issue 1 (8th December 2016) - Marygold, Steven J.; Antonazzo, Giulia; Attrill, Helen; Costa, Marta; Crosby, Madeline A.; dos Santos, Gilberto; Goodman, Joshua L.; Gramates, L. Sian; Matthews, Beverley B.; Rey, Alix J.; Thurmond, Jim; ,
Abstract: FlyBase (flybase.org) is the primary online database of genetic, genomic, and functional information about Drosophila species, with a major focus on the model organism Drosophila melanogaster . The long and rich history of Drosophila research, combined with recent surges in genomic‐scale and high‐throughput technologies, mean that FlyBase now houses a huge quantity of data. Researchers need to be able to rapidly and intuitively query these data, and the QuickSearch tool has been designed to meet these needs. This tool is conveniently located on the FlyBase homepage and is organized into a series of simple tabbed interfaces that cover the major data and annotation classes within the database. This unit describes the functionality of all aspects of the QuickSearch tool. With this knowledge, FlyBase users will be equipped to take full advantage of all QuickSearch features and thereby gain improved access to data relevant to their research. © 2016 by John Wiley & Sons, Inc.